Community interventions improve diabetes management and oral health in type 2 diabetes patients with chronic periodontitis - Yi Zhang; Yijia Chen; Chenchen Wang; Hao Xu; Nan Zhou; Xin Hong (Scientific Reports)
Abstract Type 2 diabetes mellitus (T2DM) and chronic periodontitis are interrelated chronic conditions that exacerbate each other’s progression. Despite their bidirectional relationship, oral health remains undervalued in diabetes management, particularly in underserved populations. The objective of this study was to assess whether a combined diabetes-periodontitis self-management intervention outperforms single-disease management in improving clinical outcomes, psychological well-being, and oral health in T2DM patients with chronic periodontitis. A randomized controlled trial was conducted across 12 community health centers in Nanjing, China, from June 2022 to June 2023. The participants (n = 784) were stratified into four groups, including G0 (control group, routine management), G1 (periodontal intervention), G2 (diabetes intervention), and G3 (comprehensive intervention), with 196 participants in each group. The control group (G0) received routine community-based diabetes management, while the intervention group (G1-G3) underwent a specialized self-management model-based intervention in addition to the routine management provided to the control group. The 3-month intervention included peer-led education on diabetes self-management, oral hygiene practices, dietary guidance, psychological support, and more. Outcomes [glycemic control, self-efficacy, quality of life (QoL), and oral health] were assessed at baseline (T0) and at 0 months (T1), 3 months (T2), and 6 months (T3) postintervention. Generalized estimating equations (GEEs) adjusted for covariates were used for longitudinal analysis. Compared with the other groups, the comprehensive intervention group (G3) had superior outcomes. At 3 months postintervention (T2), G3 showed the greatest improvements over G0 in terms of the fasting plasma glucose (FPG) control rate (B = 0.559, P = 0.027) and the glycated hemoglobin (HbA1c) control rate (B = 0.615, P = 0.007), alongside notable enhancements in self-efficacy (T1: B = 0.413, P = 0.020) and QoL (health utility: B = 0.025, P = 0.010). Specifically, compared with G0, G3 demonstrated marked improvements in oral health outcomes, including reduced gingival bleeding (B = − 0.751, P = 0.015), swelling (B = − 0.780, P = 0.018), tooth mobility (B= − 0.860, P = 0.007), chewing weakness (B = − 0.916, P = 0.015) and halitosis (B = − 0.763, P = 0.026). This study demonstrated that a community-based, integrated self-management intervention significantly improved glycemic control, self-efficacy, QoL, and oral health in T2DM patients with chronic periodontitis. By empowering patients through education and peer support, this model offers a scalable solution for underserved populations.